THE TERM STRUCURE OF INTEREST RATE IN A SFC MODEL WITH INFLATION TARGETING AND ZERO MONEY FINANCING OF GOVERNMENT DEFICIT - Oreiro, José Luis; Santos, Julio Fernando Costa (Práticas de Administração Pública, 2021)
The aim of the present paper is to build an SFC Post-Keynesian growth model for a closed economy with government activities that incorporates the Institutional Arrangement of fiscal and monetary policy that exists in many countries of the real world. More precisely in our model monetary policy will be conducted under the framework of Inflation Targeting Regime, direct money financing of government deficit will be forbidden by law and government issued interest rate-indexed bonds in order to finance its fiscal deficit. Hence the model is used to analyze the effects of a once-and-for all change in the level of government expenditures over the time path of investment to GDP ratio, profit share, capacity utilization, the spread between long-term and short-term interest rates and inflation. The results of the simulation show that a permanent increase in the level of government expenditures is followed by a permanent decrease in the investment to GDP ratio, a permanent increase in the spread between long and short-term interest rate, a permanent decrease in the level of capacity utilization and a permanent increase in the profit share, but with no lasting effects over inflation dynamics.